Non-linear Dynamics of CuO-MgO-TiO_2-H_2O Ternary Nanofluid Flowing Past a Rotating Cone in the Presence of Thermal Radiation - Manjunatha, S.; Puneeth, V. (Journal of Applied Nonlinear Dynamics, 2026)
The flow of ternary nanofluid past a rotating cone has been analysed using the Ternary nanofluid model. The ternary nanofluid is formed by suspending CuO, MgO and TiO_2 nanoparticles into water. The nanoparticles that are suspended in the base fluid are assumed to be in the shape of a sphere so that there will be minimum friction between the nanoparticles and the surface as a result this will allow the fluid to flow with less frictional force. Such a characteristic flow finds application in automobiles, production industries, metallurgical process, solar appliances etc. Hence, in order to analyse the heat transfer characteristics of ternary nanofluid, a mathematical model is framed with the help of partial differential equations considering thermal radiation and heat source/sink to achieve realistic results. These equations are further transformed to non-linear differential equations that are solved using RKF-45 technique. The results of this study are interpreted graphically for various parameters corresponding to the fluid flow. The outcomes of this study indicated that the increase in convection enhanced the tangential velocity of the flow and the nanofluid temperature. Whereas, the increase in the thermal slip reduced the tangential flow velocity as well as the temperature of the nanofluid.